DOES SPIRITUALITY GIVE AN IMPACT TO WELL-BEING OF ENTREPRENEUR? - Wuri, Wulan Wiyat; Andriani, Prima; Utama, Radikal Yudha (Universitas Muhammadiyah Yogyakarta, 2019)
Spirituality directs individuals to be more supportive in various work activities, especially in entrepreneurship context. This study examine the effect of subjective spirituality on entrepreneurs’ well-being by using data from the Indonesian Family Life Survey (IFLS) from 2007 to 2014. We dissect the analysis into three groups that are self-employed, business owner or employer, and employee. The result stated that spirituality does matter only for those who run the business as self-employed in terms of generating income, although they tend to have lower levels of well-being rather than those who run businesses as business owners and those who work as employees within company. We found no significant evidence that spirituality affects the well-being of business owners, on the other hand this group has the highest level of well-being. The contributions of the study are explained further in this paper